The prognostic and predictive power of redox rotein expression for anthracycline-based chemotherapy response in locally advanced breast cancer - Woolston, Caroline M.; Zhang, Lei; Storr, Sarah J.; Al-Attar, Ahmad; Shehata, Mohamed; Ellis, Ian O.; Chan, Stephen Y.; Martin, Stewart G. (Nature Publishing Group, 2012)
Neoadjuvant chemotherapy has become the standard of care for locally advanced primary breast cancer. Anthracycline-based regimens have proven to be one of the most effective treatments in this setting. As certain cytotoxic antineoplastic agents, such as anthracyclines, generate reactive oxygen species as a by-product of their mechanism of action, we examined whether redox protein expression was involved in the response to anthracycline-based chemotherapy and with clinical outcome. Pre treatment needle core biopsy and postanthracycline treatment tumour sections were analysed from 98 cases. In all, 32 individuals had a complete clinical response and 17 had a complete pathological response. Immunohistochemical staining was performed for eight redox proteins: thioredoxin, thioredoxin reductase thioredoxin interacting protein (TxNIP), glutathione S-transferase (GST) p, h and a, catalase and manganese superoxide dismutase. GST p (P¼0.05) and catalase (P¼0.045) were associated with pathological complete response in pre-chemotherapy samples. TxNIP (P¼0.017) and thioredoxin reductase (P¼0.022) were independent prognostic factors for distant metastasis free survival and TxNIP for overall survival (P¼0.014). In oestrogen receptor negative patients that are known to have a poor overall survival, a considerably worse prognosis was seen in cases that exhibited low expression of TxNIP (P¼0.000003), stratifying patients into more defined groups. This study indicates the importance of redox regulation in determining breast cancer response to anthracycline-based chemotherapy and provides ways of further stratifying pre-chemotherapy patients to potentially allow more tailored treatments.